Manganese oxidation by Leptothrix discophora. - Boogerd, F C (1987)
Cells of Leptothrix discophora SS1 released Mn2+-oxidizing factors into the medium during growth in batch culture. Manganese was optimally oxidized when the medium was buffered with HEPES (N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid) at pH 7.5. Manganese-oxidizing activity in the culture medium in which this strain had been grown previously was sensitive to heat, phosphate, Tris, NaN3, HgCl2 NaCl, sodium dodecyl sulfate, and pronase; 0.5 mol of O2 was consumed per mol of MnO2 formed. During Mn2+ oxidation, protons were liberated. With sodium dodecyl sulfate-polyacrylamide gel electrophoresis, two protein-containing bands were detected in the spent culture medium. One band had an apparent molecular weight of 110,000 and was predominant in Mn2+-oxidizing activity. The second product (Mr 85,000) was only detected in some cases and probably represents a proteolytic breakdown moiety of the 110,000-Mr protein. The Mn2+-oxidizing factors were associated with the MnO2 aggregates that had been formed in spent culture medium. After solubilization of this MnO2 with ascorbate, Mn2+-oxidizing activity could be recovered.